LINGKUNGAN KERJA, KARAKTERISTIK INDIVIDU DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN DI SOLO SQUARE MALL - LENI PUJI LESTARI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
The purpose of this study is to determine the work environment, individual characteristics and career development of employee job satisfaction at Solo Square Mall. This type of research is quantitative. This research is intended for employees who work at Solo Square Mall. The population is 1000 employees and the sample taken is 100 respondents, using random sampling techniques. The analysis method uses multiple linear regression with SPSS software version 21. F test results show that the work environment, individual characteristics and career development have a simultaneous and significant influence on employee job satisfaction at Solo Square Mall, while the results of the t test show that the work environment and characteristics individuals do not have a significant effect on job satisfaction, but career development has a significant effect on employee job satisfaction at Solo Square Mall